The contingent valuation of natural parks : assessing the warmglow propensity factor - Nunes, Paulo A. L. D.; New horizons in environmental economics (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2002)
This book provides a very detailed account of a state-of-the-art application of the contingent valuation (CV) method. The contingent valuation technique for measuring the economic value of environmental goods and services has becoming increasingly popular in recent years and has many advantages over other revealed or stated preference methods. It has been criticised, however, for being inconsistent with economic theory by reflecting altruistic motives and moral obligations. This book examines the role of the 'warmglow' effect (the pleasure derived from giving to good causes or being concerned about the environment) in contingent valuation studies and examines whether warmglow is an underlying force in CV responses.
Includes bibliographical references (p. 239-250) and index.
lje 24/08/16
Loans
Keywords: Contingent valuation; Parks